(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article highlights the role and effectiveness of cultural and educational activities in developing the spiritual and moral education of student youth in higher educational institutions. It analyzes the use of national values as the main criterion in the educational system, involving students in collective work, and creating a healthy environment among them.